Produksi konsentrat karetenoid dari fraksi cair minyak menggunakan metode kromotografi - Nur Wulandari (Jurnal Ilmu Pertanian Indonesia, 2007)
This research was aimed to obtain an optimum conditions for production of liquid fraction of crude palm (CPO) containing high concentration of  carotenoids,as well as to get  the optimum condition on production o carotenoids concentrate, by  using adsorption column chromatography method at laboratory scale. Adsorbent used  were rice hull ash and silica gel.  In order to get  high amount of carotenoids on liquid fraction of palm o the   palm oil was  treated with  n-hexane and   was  mixed by  using shaker.  Based  on  recovery and  tot carotenoids parameters contained in the  liquid fraction, the optimum condition to get high total carotenoids o liquid fraction was shown when employing 50% hexane,mixing at 200 rpm for 10 minutes,and decanting for days  at ambient temperatures. The  palm oil liquid fraction contained 275 ppm carotenoids with 81.0 recovery. The  next step   was the separation of  carotenoids from other components of palm oil by  usin adsorption column chromatography method with  rice hull ash  and  silica   gel  as  adsorbents. The optimu condition on  separation were found by  using ratio of rice hull ash:silica gel  30:10, which produced total corotenoids  of 317.2 11g   and   recovery  of   carotenoids  of   41.7%. The final  concentration in  carotenoi concentrate was 1865.9 ppm,4 times higher than the initial concentration in CPO. Key words: carotenoids,palm oil,adsorption column hromatography